Predictors of Oral Rehydration Therapy use among under-five children with diarrhea in Eastern Ethiopia: a community based case control study - Mengistie Bezatu; Berhane Yemane; Worku Alemayehu (BMC, 2012)
Abstract Background Rehydration therapy is a critical intervention to save the lives of children during the episodes of diarrhea. However, millions of children die every year due to failure to replace fluid effectively. The objective of this study was to identify the predictors of Oral Rehydration Therapy use among under-five children with diarrhea. Method A community based unmatched case control study was conducted in Kersa district, Eastern Ethiopia, in February, 2011. The cases were 241 under-five children with diarrhea in the preceding two weeks before the survey and who had received Oral Rehydration Therapy while the controls were 253 under-five children with diarrhea in the preceding two weeks before the survey and who had not received Oral Rehydration Therapy. The cases and the controls were compared to find out the factors that were associated with the utilization of Oral Rehydration Therapy. Result The study revealed that caregivers' previous experience of Oral Rehydration Therapy use (AOR = 4.05, 95% CI = 2.63-6.22), seeking advice or treatment from health facilities, (AOR = 3.25, 95% CI = 2.06-5.11) and knowledge of Oral Rehydration Therapy (AOR = 3.09, 95% CI = 1.97-4.85) were found to be the positive determinants of Oral Rehydration Therapy use. Perception of teething as a cause of diarrhea was negatively associated with the utilization of Oral rehydration Therapy (AOR = 0.61, 95% CI = 0.37-0.98). Conclusion Health education should be strengthened on the benefit, preparation, early initiation of Oral Rehydration Therapy and the causes of diarrhea. Attention should be given to those who do not have previous experience of Oral Rehydration Therapy use and have less frequent contacts with the health facilities.